Project risk management : a practical implementation approach - Bissonette, Mike (Project Management Institute, Inc., 2016)
There is no question that risk management is critical for project success. In today's fast-paced, constantly changing, and highly competitive environment, risk management is more important than ever in all industries across the globe. Risk management should therefore be considered a vital component of any project management practitioner's training. In 'Project Risk Management: A Practical Implementation Approach, ' Mike Bissonette provides insights into the best ways of implementing traditional techniques of risk management and also explores innovative methods that can help modern organizations build their culture, improve financial performance, and ultimately achieve greater success in all their projects. This holistic approach to risk management expands on the subject by considering how project manager competencies, as well as stakeholder influences, affect risk not only at the individual project level, but also at the program and portfolio levels, offering a long view on continuous improvement of organizational excellence.
Keywords: Project management.; Risk management.; elektronické knihy; electronic books